Personal Hygiene and Worm Eggs at Pupils Nail in Kupang City, Indonesia - Enni Rosida Sinaga; Erika Maria Resi; Wanti Wanti (International Journal of Public Health Science (IJPHS), 2016)
Worm disease does not cause death but can affect digestion, absorption and metabolism of food. Helminthiasis figure in Kupang City in particular were not recorded properly, but when viewed from its risk factor then it was endemic because of sanitary conditions, personal hygiene, behavior, and the provision of clean water is still low. This study aim to identify the presence of worm’s eggs in the pupils nail and the correlation with clean and healthy living behavior of pupils. This analytic observational study used cross sectional design. The samples were primary school students as many as 50 people that were taken by random sampling. Data collection was through interviews and laboratory tests on stool samples and analyzed by using chi-square. Results found as many as 13 pupils (26%) were infested by worm eggsof Ascaris lumbricoides at their nail. There were no relation between the presence of worm eggs at pupils nail with gender (p=0.303), age (p=0.747), grade (p=0.643) and playing habits (p=1.000), but there is an association between the presence of worm eggs at elementary pupils nails with the latrine use (p=0.049) and personal hygiene (p=0.039). So that PHC expected to cooperate with the department of education improve the promotion and provision of facilities to support a clean and healthy behaviors for elementary school students.